IoT and Data Spaces as a highly distributed measurement and control system = IoT i Data Spaces jako wysoce rozproszony system pomiarów i sterowania - Koropiecki, Igor; Piotrowski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
Ongoing digital transformation creates new challenges for interoperability between distributed measurement platforms. The European Union introduces data spaces, which are on their way to become the standard for trusted data exchange between stakeholders. This proliferation creates new opportunities for value generation through data, service and application markets. The paper discusses the challenges of adapting existing concepts to create solutions for the emerging ecosystem of data-driven transactions.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne